Brown tumor as an unusual but preventable cause of spinal cord compression: Case report and review of the literature - Tayfun, Hakan; Metin, Orakdögen; Hakan, Somay; Zafer, Berkman; Vardar, Aker (Asian Journal of Neurosurgery, 2014)
Brown tumor (BT), also known as osteoclastoma, may appear in the context of primary and secondary hyperparathyroidism. Spinal cord compression due to the BT is extremely rare. We present here an unusual case of BT involving thoracal spine and mandible. A 26-year-old woman, who had been on hemodialysis for chronic renal failure for over 6 years, got admitted with dorsal pain and progressive weakness in her lower extremities and gait disturbances. Neurological examination revealed spastic paraparesis and symmetrically hyperactive tendon reflex in the lower extremities. She had hypoesthesia under T10 level. On physical examination, a swelling on the left side of her jaw was also detected. Magnetic resonance imaging (MRI) showed cord compression due to an extradural mass lesion at T8 level. A computerized tomography (CT) scan showed that this expansile lytic lesion was caused by the collapse of vertebra corpus (T8) at that level. CT of the mandible revealed an expansile lytic lesion on left arm of the mandible. Laboratory findings were nearly normal except parathormone level elevation to 1289 pg/mL (normal 30-70 pg/mL). Ultrasound examination showed enlargement of the parathyroid glands. The patient underwent an emergency decompression and stabilization surgery. The lesion was fragile and reddish in appearance and was easy to aspirate. The tumor was reported as "BT." Her weakness in the lower extremities improved in the early postoperative period. Following surgical intervention, the patient was transferred to nephrology clinic for additional medical treatment.
Keywords: Brown tumor; hyperparathyroidism; osteitis fibrosa cystica; spinal cord compression; spine